Manual of security sensitive microbes and toxins - Liu, Dongyou (Boca Raton : CRC Press, Taylor and Francis, 2014)
Security sensitive microbes (viruses, bacteria, fungi, and parasites) and toxins, which are often referred to as the select agents and toxins, have the capacity to cause serious illness and death in humans, animals, and plants. Throughout history, these microbes and toxins have been exploited in one form or another as biowarfare and bioterror agents that create fear and panic well beyond any actual physical damages they might cause. Manual of Security Sensitive Microbes and Toxins provides comprehensive, state-of-the-art coverage of microbes and toxins of biosecurity concern.
Section 1. Microbes and toxins affecting humans and animals : viruses -- section 2. Microbes and toxins affecting humans and animals : bacteria -- section 3. Microbes and toxins affecting humans and animals : fungus and parasite -- section 4. Microbes and toxins affecting humans and animals : toxins -- section 5. Microbes affecting animals : viruses -- section 6. Microbes affecting animals : bacteria -- section 7. Microbes affecting plants.
Includes bibliographical references and index.
Keywords: Virus diseases; Bacterial infections; Communicable Disease Control; Mycoses; Parasitic diseases; Toxins, Biological